A Practical Guide for Using Electrochemical Dilatometry as Operando Tool in Battery and Supercapacitor Research. Issue 5 (10th March 2022) - Escher, Ines; Hahn, Matthias; A. Ferrero, Guillermo; Adelhelm, Philipp
Abstract : Lithium‐ion batteries and related battery concepts show an expansion and shrinkage ("breathing") of the electrodes during cell cycling. The dimensional changes of an individual electrode or a complete cell can be continuously measured by electrochemical dilatometry (ECD). The obtained data provides information on the electrode/cell reaction itself but can be also used to study side reactions or other relevant aspects, e.g., how the breathing is influenced by the electrode binder and porosity. The method spans over a wide measurement range and allows the determination of macroscopic as well as nanoscopic changes. It has also been applied to supercapacitors. The method has been developed already in the 1970s but recent advancements and the availability of commercial setups have led to an increasing interest in ECD. At the same time, there is no "best practice" on how to evaluate the data and several pitfalls exist that can complicate the comparison of literature data. This review highlights the recent development and future trends of ECD and its use in battery and supercapacitor research. A practical guide on how to evaluate the data is provided along with a discussion on various factors that influence the measurement results. Abstract : Electrochemical dilatometry is a powerful operando technique to measure the thickness change in an electrochemical device during cycling. Several studies have been published in recent years, investigating batteries and supercapacitors. This review presents selected examples from literature, a guideline on how to evaluate dilatometry data, and gives information on which effects have an influence on the data.